Analisis Strategi Penerjemahan dalam Novel “Murder on the Orient Express” Karya Agatha Christie - Syahnia, Riska; Gusthini, Misyi (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
The novel Murder on the Orient Express by Agatha Christie is a classic masterpiece in the mystery genre that requires accuracy in translating the nuances of language and cultural context so that the message and tone of the story can be conveyed well in the target language. This study aims to analyze the translation strategies used in the novel Murder on the Orient Express. The author observes a void in research related to translation strategies for the novel Murder on the Orient Express. Therefore, the author considers that this research needs to be conducted. The research method used by the author is the qualitative research method. In analyzing the novel, the author refers to the theory of translation strategies described by Suryawinata and Hariyanto (2016). Suryawinata and Hariyanto (2016) mentioned three translation strategies: structural, semantic, and pragmatic. The data in this study are in the form of phrases or sentences from the novel Murder on the Orient Express (2011) and their equivalents from the translated novel titled Pembunuhan di Orient Express (2024). The analysis results show that almost all of the sub-strategies from the three translation strategies are used in this novel. However, one translation strategy is not used in the novel, namely transediting.